The city of Millo. The wall as an urban highlighter. - Caterina Palestini (Disegnare con)
<span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: IT; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The contribution proposes an analysis conducted on the drawings made, in many walls of peripheral neighborhoods in Italy and in the world, by Millo, the street artist architect that as a recurrent theme depicts an anonymous and infinitely replicable city on which to highlight themes that make one reflect. The interpretation of the city comes from his studies, the architecture constitutes the distinctive element of the works and is used as an urban backdrop, as a regulating path of a three-dimensional spatiality generated by a clear and sure sign that with constant monochrome refers to limits and dysfunctions of an unplanned urban planning, of ungreen urban contexts, that are dense of traffic, of tangled streets around buildings crossed by planes that cross the skies skimming skyscrapers. Within the three-dimensional pattern that as in a chained lego multiplies the building volumes, the human presence intervenes. The latter is fundamental in the number: one or two at most; in the forms of giant proportion; in the species: the man, the woman, the child, stylized figures that like “pure beings” aliens inhabit the city. The scenes are inspired by the critical observation of the context in which the artist works by expressing through simple daily gestures that everyone can understand, thoughts, dreams, sometimes outlined with the addition of a few colored elements that intervene to focus attention, to catch the eye of the observer and make him reflect on the meaning of the communicated theme. In summary the contribution aims at the conceptual graphic analysis of Millo’s works, investigated with a methodology that examines them by drawing, breaking down the images into abacus of components and then reassembling them in the digital dimension. The innovative aspect, supported by the digital language, allows exploring the spaces painted on the walls in three dimensions, to enter the city of Millo as if in a game, virtually following it. <span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: IT; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">DOI: https://doi.org/10.20365/disegnarecon.24.2020.21 <span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: IT; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">